PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA KEUANGAN DENGAN VARIABLE PENGHUBUNG KEPUASAN KARYAWAN DAN KUALIATAS LAYANAN PADA SEKTOR PERBANKAN DI SURABAYA - Lilianti Chiasidy; Devie Devie (Business Accounting Review, 2016)
The purpose of this study was to know whether there was significant affect of Leadership Style towards Financial Performance through Employee’s Satisfaction and Service Quality as intervening variables in banking corporate in Surabaya. The sample used in this study was banking corporate listed on Bursa Efek Indonesia (BEI) that generate profit in the last 3 years. Data analysis used Partial Least Square method with 600 respondents from 30 selected banks in Surabaya. This Study showed that there was a positive relationship of Leadership Style to Employee’s Satisfaction, Leadership Style to Service Quality, Employee’s Satisfaction to Financial Performance, Leadership Style to Financial Performance and Employee’s Satisfaction to Service Quality. And Negative relationship of Service Quality to Financial Performance.